Typification of ten species of Litsea Lam. (Lauraceae) endemic to India (Bangladesh Journal of Plant Taxonomy, 2015)
This paper deals with the lectotypification of eight binomials of seven recognized species of Litsea Lam. endemic to India, namely Litsea assamica (Meisn.) Hook. f., L. coriacea (B. Heyne ex Nees) Hook. f., L. membranifolia Hook. f., L. oleoides (Meisn.) Hook. f., L. stocksii (Meisn.) Hook. f., L. venulosa (Meisn.) Hook. f., and L. wightiana (Nees) Hook. f. Types of three other endemic species, viz. L. beddomei Hook. f., L. mishmiensis Hook. f. and L. oreophila Hook. f. are also specified.Bangladesh J. Plant Taxon. 22(2): 77-81, 2015 (December)